Social Influence Through Word-of-Mouth Communications in Social Networking - Osborne, Delane Julia (Curtin University, 2018)
A study contributing to the existing literature by conceptualising a holistic model of the operation of word-of-mouth communications. Operationalized through a mixed methods research design, the study provides empirical evidence of the existence of influence from brand related word-of-mouth communications exchanged on social networking sites. Considering the impact of this influence on the consumption behaviours of individuals, results from the study have practical implications for marketing practitioners utilising social media as a marketing tool.